Lactococcus garvieae: a small bacteria and a big data world. Issue 1 (December 2015) - López-Campos, Guillermo; Aguado-Urda, Mónica; Blanco, María; Gibello, Alicia; Cutuli, María; López-Alonso, Victoria; Martín-Sánchez, Fernando; Fernández-Garayzábal, José
Abstract Objective To describe the importance of bioinformatics tools to analyze the big data yielded from new "omics" generation-methods, with the aim of unraveling the biology of the pathogen bacteriaLactococcus garvieae . Methods The paper provides the vision of the large volume of data generated from genome sequences, gene expression profiles by microarrays and other experimental methods that require biomedical informatics methods for management and analysis. Results The use of biomedical informatics methods improves the analysis of big data in order to obtain a comprehensive characterization and understanding of the biology of pathogenic organisms, such asL. garvieae . Conclusions The "Big Data" concepts of high volume, veracity and variety are nowadays part of the research in microbiology associated with the use of multiple methods in the "omic" era. The use of biomedical informatics methods is a requisite necessary to improve the analysis of these data.